Network characteristics of the youth’s insomnia and emotional symptoms and their gender differences - Liu, Chang; Zhou, Lie; Pi, Xiao-Xia; Liu, Bo; Zhang, Xin-Feng; Wei, Wen-Can; Nie, Suo-Cheng (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the association between sleep disorders and symptoms of depression and anxiety in the youth and to analyze the influence of gender factors.MethodsUsing the Mental Health Status Survey Questionnaire for Adolescent Students compiled by Professor Maosheng Ran, a survey was conducted and 7247 valid responses were collected (valid response rate of 79.11%). Integrating the Insomnia Severity Index(ISI), Patient Health Questionnaire(PHQ-9), and Generalized Anxiety Disorder Scale(GAD-7), network analysis was employed to assess the network structure, symptom associations, and gender differences related to insomnia, depression, and anxiety among youth.ResultsIn the network of insomnia, depression, and anxiety symptoms among youth, the highest strength centrality values were observed for “excessive worry,” “fatigue,” “sleep dissatisfaction,” and “distress caused by sleep difficulties.” Five bridge symptoms were identified: “fatigue,” “nervousness,” “suicidal ideation,” “motor,” and “guilt.” Significant differences in network structures existed between genders, specifically in network invariance (M = 0.909, p = 0.025) and global strength (males = 75.155, females = 70.527; S = 4.628, p = 0.041). Additionally, males showed significantly higher bridge strength in “anhedonia” than females (p = 0.044).ConclusionsThis study revealed that insomnia, anxiety, and depression symptoms among youth are closely interconnected. Core symptoms such as “excessive worry” and “sleep dissatisfaction,” along with bridge symptoms like “fatigue,” “nervousness,” and “suicidal ideation,” represent potential intervention targets, with fatigue playing a dual role in the network. Males require particular attention regarding the intervention of “anhedonia.” Targeted improvement of these key symptoms may help break the cycle of comorbidity and provide precise directions for mental health interventions among young people.